2016
DOI: 10.1002/ehf2.12093
|View full text |Cite
|
Sign up to set email alerts
|

Subgroup analyses of randomized clinical trials in heart failure: facts and numbers

Abstract: Subgroup analyses of major randomized clinical trials in heart failure are published frequently, but their impact on medical knowledge and practice guidelines has not been previously reported. In a novel analysis, we determined number of citations, impact factors, number of authors, and citations in guidelines of both parent trials and sub‐studies; we also qualitatively assessed whether the analyses were described as post‐hoc and non‐pre‐specified. A total of 229 sub‐studies evaluating outcomes in patient subg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…Two recent reviews investigated subgroup analysis quality in low back pain management trials 29,30 and reported the failure to specify the subgroup hypotheses a prior as a common problem in trials, which is also consistent with our findings. Vidic et al 10 reviewed phase III cardiovascular RCTs with subgroup analysis, concluding that subgroup analysis was reported with several shortcomings, including lack of prespecification and testing of a large number of subgroups without the use of the statistically appropriate test for interaction. All these studies reported the failure to specify the subgroup hypotheses, the many subgroup analyses conducted and underuse of interaction tests as common problems in trials, which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent reviews investigated subgroup analysis quality in low back pain management trials 29,30 and reported the failure to specify the subgroup hypotheses a prior as a common problem in trials, which is also consistent with our findings. Vidic et al 10 reviewed phase III cardiovascular RCTs with subgroup analysis, concluding that subgroup analysis was reported with several shortcomings, including lack of prespecification and testing of a large number of subgroups without the use of the statistically appropriate test for interaction. All these studies reported the failure to specify the subgroup hypotheses, the many subgroup analyses conducted and underuse of interaction tests as common problems in trials, which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Subgroup analysis has the potential to generate hypotheses for further prospective investigation 10 and its exploratory nature requires results to be confirmed in a new study to ensure the findings have statistical reliability. However, confirmatory studies are generally never carried out and decisions in clinical practice are made despite this lack of information.…”
Section: Introductionmentioning
confidence: 99%
“…Randomised clinical trials (RCTs) in cardiovascular disease often include subgroup analyses. 1 3 These are used to assess heterogeneity of treatment effects, concerning primary, secondary or adverse trial outcomes. 4 6 Corresponding investigations are generally based on the assumption that certain subgroups of patients may benefit more or less from a studied intervention.…”
Section: Introductionmentioning
confidence: 99%
“…This is not a call for additional subgroup analyses; they have limitations. 14 Rather, as in the case with ivabradine, we should try to deliver as much precision as we can to our list of indications (and contraindications), thereby maximizing benefit without exposing patients to undue costs and potential harm.…”
Section: Concluding Thoughtsmentioning
confidence: 99%